Cost accounting methods for construction projects in North-West Russia : case study Pöyry CM Oy - Keisala, Jouni (2010)
Pro gradu -työ : Kuopion yliopisto, kauppatieteiden laitos, yrityksen hallinto ja rahoitus, 2009. The aim of the thesis is to develop Cost Accounting methods for the Construction Project in North-West Russia. The frame of the thesis is to make the inspection of Russian, Finnish and British cost accounting methods and to analyze their differences. This comparison has been executed not only as a literature research, but also through interviews with professionals, who orientated cost accounting and project’s key persons. Activity Based Cost Accounting is added to the thesis to reach a more solid scientific base. The methods of ABC-Accounting are under research to bring benefits and to contribute to the project’s cost accounting and cost controlling. The first part of the thesis describes Russian business environment starting from historical view points to reasons for the ruble crisis. Besides the basic rules of legislation and the impact of recent day recession on Russian economy are being discussed. The results of different accounting methods inspection show that these methods differ a lot in some parts. It especially concerns the Russian cost accounting method “Smeta” which has formed so wide a system that it can be applied for the most special construction projects as well. On the other hand, the British and the Finnish cost accounting methods are limited only by general construction projects. These two methods are more transparent and clear in their structure. So they resemble each other remarkably well. Besides construction project price setting mechanism and basic assumptions are under surveillance in Finnish and Russian cost accounting methods. In Finnish method the project’s costs start to form from a bigger entity and calculations are specified step by step towards smaller entities. When the project has been divided into smaller construction particles and the price setting has been done, the document forms the basis for the project budget. In Smeta-system it’s other way round: the cost can be carried ...